Empatia e nostalgia diasporica - Serra, Carlo (Bollettino Filosofico, 2022)
The profound relationships that link the world of Husserl’s Fifth Cartesian Meditation to the problem of empathy have been the subject of much rich analysis within the study of interpretative forms of intersubjectivity. This essay interweaves the empathic theme with the world of so-called diasporic nostalgia from the perspective of a theoretical valorisation of the theme of passive synthesis. In fact, the relations linked to the synthetic forms generated by the figure-background relationship seem to constitute an ideal terrain for rethinking in anthropological terms the theme of reciprocity between differences, which Husserl uses almost obsessively in the most explicitly methodological paragraphs of that text, in a joint that aspires to solve the enigma of the empathic form. Keywords: Diasporic Nostalgia, Empathy, Logical Reciprocity, Passive Syntheses, Transculturality